Estudo da produção de biodiesel por transesterificação etílica e sua purificação utilizando processos com membranas - Gomes, Maria Carolina Sérgi (2012)
This study investigated the efficiency of micro- and ultrafiltration with ceramic membranes in separating and purifying biodiesel produced by ethylic transesterification of vegetable oils, using sodium hydroxide as a catalyst. The influence of temperature and oil:alcohol molar ratio on ethyl esters yield was evaluated by the application of a 22 factorial design and response surface methodology. According to the results, with the use of degummed soybean oil, which presented a higher acidity, maximum yield of esters was obtained at a temperature of 30 ºC and an oil:alcohol molar rate of 1:7.5. Using refined canola oil in the reaction, the highest esters yield was obtained at 45 ºC and 1:7.5. After the determination of the optimum conditions for the production of ethyl esters, the reaction mixture, produced in the optimum condition, was directly fed in a tangential micro- and ultrafiltration module to separate glycerol. Experiments were carried out with α-Al2O3/TiO2 tubular ceramic membranes with average pore size of 0.2μm, 0.1μm, 0.05 μm, and 20 kDa, and filtration area of 0.005 m2. In the first step, it was developed a methodology of acidified water addition to the reaction mixture, to promote demulsification of the mixture and, thus, the glycerol retention by the membrane. Micro- and ultrafiltration runs, with the reaction mixture produced from degummed soybean oil, were performed in batch mode with water addition of 10, 20, and 30 wt.%, at 1.0, 2.0, and 3.0 bar transmembrane pressures and 50 ºC. Membrane performance was evaluated based on the capacity of glycerol retention and on the permeate flux values. With the use of 20 wt.% water concentration, the separation was efficient, but the aqueous phase retained on the membrane surface caused a sharply flux decline. Results showed that 30 wt.% water concentration is excessive and, in almost all runs, the aqueous phase containing glycerol permeated through the membrane. The addition of 10 wt.% water, not only reduced the membrane fouling, but also promoted the glycerol retention, to that, the permeates presented glycerol content lower than 0.02 wt%, the specification limit of free glycerol in biodiesel. The best results, with 10 wt.% water addition, were obtained with the ultrafiltration membranes, 0,05 μm e 20 kDa, at 1.0 bar transmembrane pressure. Ultrafiltration of reaction mixture produced from refined canola oil was not satisfactory in removing glycerol, under all evaluated conditions. The comparison among the use of degummed soybean oil, refined soybean oil, crude canola oil, and refined canola oil, demonstrated that, free fatty acid presented in the oils influence the formation of droplets containing glycerol. The separation was efficient when reaction mixture was produced from degummed soybean oil and crude canola oil, both with a higher acidity value. In the next step, using crude canola oil, the runs were performed at 1.0, 2.0, and 3.0 bar transmembrane pressure and temperature of 50 ºC. The highest free fatty acid content in the crude canola oil, not only favored the formation of an aqueous phase containing glycerol, which was retained by the membrane, but also resulted in the lowest flux decline rates. The ultrafiltration was efficient in removing glycerol, since the highest glycerol content in the permeate was 0.013 wt.%. Finally, it was conducted the analysis of fouling mechanisms using a model proposed in the literature applied to cross-flow filtration and constant pressure. Using 10 wt.% water concentration, for both degummed soybean oil and crude canola oil, the predominant fouling mechanism was the complete pore blocking. With 20 and 30 wt.% water, the predominant fouling mechanisms were cake filtration and internal pore blocking respectively. The fouling mechanism dominant in each experimental condition is dependent upon the size of aqueous phase droplets and the membrane pore diameter. This novel refining process of biodiesel showed the advantage of not requiring previous decantation to separate the two phases obtained after transesterification and the reduction in the amount of water used in the washing steps, thus minimizing the environmental impact of the biodiesel production process. The properties of the biodiesel produced, which were evaluated, meet the ANP biodiesel standards required for marketing.